Peluang Pengembangan Ekonomi Kreatif di Era Society 5.0 bagi Generasi Milenial - Rusmini, M. E; Alifatul Laili Masfiah; Mh. Taufiqur Rohman; Putri Amelia Amanda; Shofiana Firdaus Zahro (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2022)
Currently, in the global or digital era, the creative economy is in the spotlight because of its beneficial impact on the Indonesian economy. Even though globalization in the economic sector has the potential to become a problem for the Indonesian population as a whole, especially the millennial generation, which must be addressed immediately, the millennial generation remains the main creative force in the economy. The purpose of this research is to understand the economic situation in Indonesia considering that the creative industry is being loved by the younger generation. This type of research uses quantitative and qualitative methods. The results of the study show that advances in technology and communication in the era of the digital revolution have changed Indonesia's business sector, namely the creative economy. Millennials with strong creativity will be able to shape their own direction of development, and the creative economy will also benefit them financially or vice versa by giving them an advantage. Especially Jember Regency, has encouraged the younger generation or the current generation to participate in the development of the creative economy.